Predicting factors of preventive and control behaviors of communicable diseases in children among teachers in child care centers, Bangkok Metropolitan Administration - Chanpong, Sirinapha; Nakakasien, Piyathida; Krinuwat, Keerada (Chulalongkorn Medical Journal, 2020)
Background: Communicable diseases have become a major cause of death for children under the age of five years all over the world. Illness at this age will affect the growth, development and overall health of children. Objectives: The aim of this study was to determine the predictive factors of preventive and control behaviors of teachers for communicable diseases in children in child care centers, Bangkok Metropolitan Administration (BMA). Methods: The subject group consisted of 112 teachers and simple sampling selection criteria was: child care teacher working in child care centers for at least 1 year were recruited. The data were collected between April - May 2019 using personal data questionnaires, health literacy questionnaires, preventive and control behaviors of communicable diseases questionnaires. Results: The results showed that age, experience of being a teacher, experience of training about communicable diseases, and health literacy of preventive and control of communicable diseases in children were able to predict 17.6 % (R2 = 0.176, P < 0.001). It was found that only health literacy on preventive and control of communicable diseases was able to predict the preventive behavior of communicable diseases in children with statistical significance ( = 0.42, P < 0.001). Conclusion: Teacher’s health literacy of preventive and control of communicable diseases in children is important. Teachers should be provided with guidelines for the development of health literacy for preventive and control of communicable diseases in children which could lead to healthy children in child care centers.